Pengaruh Cara Pengeringan Terhadap Sifat Fisik, Kimia dan Tingkat Kesukaan Seduhan Bubuk Bunga Telang Kering - Aflah Athallah Majid Majid; Siti Tamaroh Cahyono Murti; Dwiyati Pujimulyani (Journal of Food and Agricultural Technology, 2025)
Butterfly pea flowers have potential as an herbal plant with benefits for the body. Butterfly pea flower tea is purple in color due to anthocyanin pigments, which have high antioxidant activity. Butterfly pea flowers are perishable, so drying can be used to extend their shelf life. In this study, drying was carried out using two methods, namely a cabinet dryer and sunlight. The dried blue pea flowers were then brewed with water at various pH levels to determine panelist preferences and antioxidant properties, with the addition of lime juice at varying pH levels. In this study, butterfly pea flowers were dried in a cabinet dryer for 9 hours and in the sun for 8 hours. The dried butterfly pea flowers were then brewed with water at pH 3, pH 5, and pH 7. The results showed that the brew from sun-dried flowers was preferred by the panelists. The brew with water at pH 3 was preferred over the other treatments. The brew had the following criteria: L*, a*, and b* values of 31.99, 13.94, and -2.87, respectively; moisture content of 5.53%; antioxidant activity of 33.12% (RSA); and total phenol content of 182.65 mg EAG/g.